2019
DOI: 10.4049/jimmunol.1900899
|View full text |Cite
|
Sign up to set email alerts
|

Platelets in Inflammation and Resolution

Abstract: Platelets have long been known for their role in hemostasis. In this, platelet adhesion and activation leads to the formation of a firm thrombus and thus the sealing of a damaged blood vessel. More recently, inflammatory modes of function have been attributed to these non–nuclei-containing cellular fragments. Interaction with leukocytes, secretion of proinflammatory mediators, and migratory behavior are some of the recent discoveries. Nonetheless, platelets also have anti-inflammatory potential by regulating m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
112
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(114 citation statements)
references
References 181 publications
(166 reference statements)
1
112
0
1
Order By: Relevance
“…blocking the viral invasion has become necessary; and 4) Yang et al also showed that mortality decreased with the increasing of the platelet count, suggesting the thrombotic process has abated and platelets are no longer consumed into the clot [60]. In addition, platelets also have an anti-in ammatory potential by regulating macrophage functions, regulatory T cells, and secreting pro-resolving mediators [61]. All those observations concur with the ndings of the present study, in which the increase in platelets correlated with less in ammation (reduced CRP levels), an increase in total lymphocytes, and clinical improvement in the patients (a lower patient overall self-assessment score).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…blocking the viral invasion has become necessary; and 4) Yang et al also showed that mortality decreased with the increasing of the platelet count, suggesting the thrombotic process has abated and platelets are no longer consumed into the clot [60]. In addition, platelets also have an anti-in ammatory potential by regulating macrophage functions, regulatory T cells, and secreting pro-resolving mediators [61]. All those observations concur with the ndings of the present study, in which the increase in platelets correlated with less in ammation (reduced CRP levels), an increase in total lymphocytes, and clinical improvement in the patients (a lower patient overall self-assessment score).…”
Section: Discussionmentioning
confidence: 99%
“…Jecko Thachil (2020) correctly interpreted those results [ 60 ] as follows: 1) the ‘higher’ platelet counts for an illness as severe as COVID-19 is unusual, and likely points towards liver activation and thrombopoietin release; 2) the lung-specific entry of SARS-CoV-2 suggests that the lung megakaryocytes, in response to liver thrombopoietin, locally produce a large number of platelets to help with the defense of the host; 3) the reduction of platelets in patients with severe disease could be due to the fact that the platelets are being consumed to form pulmonary thrombi, which occurs when multiple efforts (including those of the platelets) to stop the infection have not succeeded, and blocking the viral invasion has become necessary; and 4) Yang et al also showed that mortality decreased with the increasing of the platelet count, suggesting the thrombotic process has abated and platelets are no longer consumed into the clot [ 60 ]. In addition, platelets also have an anti-inflammatory potential by regulating macrophage functions, regulatory T cells, and secreting pro-resolving mediators [ 61 ]. All those observations concur with the findings of the present study, in which the increase in platelets correlated with less inflammation (reduced CRP levels), an increase in total lymphocytes, and clinical improvement in the patients (a lower patient overall self-assessment score).…”
Section: Discussionmentioning
confidence: 99%
“…Over the last decades, accumulating evidence has demonstrated that platelets contribute importantly to the inflammatory microenvironment of atherosclerosis, such as recruitment of inflammatory cells, 2,3,6,7 macrophage polarization, 7,8 neutrophil extracellular trap (NET) formation, 9 and inflammation resolution 10 . We and others have shown that platelets can regulate multiple aspects of CD4 + T cell activities 3,5,10,11 . Activated platelets release various CD4 + T cell‐active mediators, such as platelet factor 4 (PF4), transforming growth factor β (TGFβ), thromboxane A 2 (TxA 2 ) and RANTES (regulated upon activation, normal T cell expressed and presumably secreted).…”
Section: Introductionmentioning
confidence: 99%
“…Platelets are enucleate cells and have critical roles in thrombosis, homeostasis and the in ammatory response [18]. When the internal envir MPV detection and assays are generally valid in the clinic as they are routinely performed.…”
Section: Introductionmentioning
confidence: 99%